Oscillation of Second Order Nonlinear Neutral Differential Equations - Yingzhu Wu; Yuanhong Yu; Jinsen Xiao (Mathematics, 2022)
The study of the oscillatory behavior of solutions to second order nonlinear differential equations is motivated by their numerous applications in the natural sciences and engineering. In the presented research, some new oscillation criteria for a class of damped second order neutral differential equations with noncanonical operators are established. The results extend and improve on those reported in the literature. Moreover, some examples are provided to show the significance of the results.